Real-world treatment patterns and survival outcomes in men with metastatic castration-resistant prostate cancer in Finland: a national, population-based cohort study - Antti Rannikko; Olivia Hölsä; Trude Ågesen; Mattias Ekman; Riikka Mattila (Acta Oncologica)
Background: Metastatic castration-resistant prostate cancer (mCRPC) treatment is advancing yet Nordic, real-world evidence for its use is scarce. In this population-based cohort study, we describe characteristics of patients with mCRPC, and their treatment patterns and survival outcomes in Finland.